Lenalidomide/melphalan/dexamethasone in newly diagnosed patients with immunoglobulin light chain amyloidosis: results of a prospective phase 2 study with long-term follow up - Hegenbart, Ute; Bochtler, Tilmann; Benner, Axel; Kimmich, Christoph; Kristen, Arnt; Beimler, Jörg; Hund, Ernst; Zorn, Markus; Freiberger, Anja; Peters-Gawlik, Marianne; Goldschmidt, Hartmut; Hose, Dirk; et al. (Haematologica, 2017)
Chemotherapy in light chain amyloidosis aims to normalize the involved free light chain in serum, which leads to an improvement, or at least stabilization of organ function in most responding patients. We performed a prospective single center phase 2 trial with 50 untreated patients not eligible for high-dose treatment. The treatment schedule comprised 6 cycles of oral lenalidomide, melphalan and dexamethasone every 4 weeks. After 6 months, complete remission was achieved in 9 patients (18%), very good partial remission in 16 (32%) and partial response in 9 (18%). Overall, organ response was observed in 24 patients (48%). Hematologic and cardiac toxicities were predominant adverse events. Mortality at 3 months was low at 4% (n=2) despite the inclusion of 36% of patients (n=18) with cardiac stage Mayo 3. After a median follow-up of 50 months, median overall and event-free survival were 67.5 months and 25.1 months, respectively. We conclude that the treatment of lenalidomide, melphalan and dexamethasone is very effective in achieving a hematologic remission, organ response and, consecutively, a long survival in transplant ineligible patients with light chain amyloidosis. However, as toxicity and tolerability are the major problems of a 3-drug regimen, a strict surveillance program is necessary and sufficient to avoid severe toxicities. clinicaltrials.gov Identifier: 00883623 (Eudract2008-001405-41).